Inhibitory effect of fucoidan on TNF-α-induced inflammation in human retinal pigment epithelium cells - Lee, Sol; Lee, Eun Jeoung; Lee, Gyu Min; Yun, Ji-Hyun; Yoo, Wonbeak (Frontiers in Nutrition, 2023)
Sagassum horneri (S. horneri) is a brown seaweed that contains a fucose-rich sulfated polysaccharide called fucoidan and is known to possess beneficial bioactivities, such as anti-inflammatory, antiviral, antioxidative, and antitumoral effects. Owing to its biological activities, S. horneri has been used in biomedical, functional food, and technological applications. This study aimed to determine the anti-inflammatory effects of AB_SH (hydrothermal extracts from S. horneri) and its bioactive compound (fucoidan) against tumor necrosis factor alpha (TNF-α)-induced inflammation in human retinal pigment epithelial (RPE) cells. AB_SH did not exhibit any cytotoxicity, and it decreased the mRNA expression of interleukin (IL)-6 and IL-8 and the production of the cytokines IL-6 and TNF-α. It also suppressed the expression levels of phosphorylated nuclear factor kappa B (NF-κB) and mitogen-activated protein kinases (MAPKs), including c-Jun amino-terminal kinases (JNK), p38 protein kinases (p38), and extracellular signal-regulated kinase (ERK) proteins, suggesting that AB_SH inhibits activation of the NF-kB/MAPK signaling pathway. Since fucoidan was identified in the composition analysis of AB_SH, it was additionally shown to be required for its anti-inflammatory effects in TNF-α-stimulated human RPE cells. In line with the AB_SH results, fucoidan reduced the mRNA levels of IL-6, IL-1ß, and IL-8 and production of the cytokines IL-6, TNF-α, and IL-8 through the downregulation of the NF-kB/MAPK signaling pathway in a dose-dependent manner. Collectively, the ability of AB_SH from S. horneri hydrothermal extracts to reduce inflammation indicates that it may be a good functional ingredient for managing ocular disorders.